Komunista the genesis of the Philippine Communist Party, 1902-1935 - Richardson, Jim 1947- (Quezon City Ateneo de Manila University Press, 2011)
"Komunista presents a most comprehensive and detailed history of the beginnings of what eventually became the Partido Komunista ng Pilipinas. It traces the roots of the movement to the labor federation formed from among gremios or guilds, neighborhood associations, and trade or shop associations of printers, tabaqueros, tailors, sculptors, seamen, and cooks. It provides portraits of the movement's leadership as it evolved through the years, notably citing personalities such as Isabelo de los Reyes, Juan Feleo, and Crisanto Evangelista."--Provided by publisher.
Includes bibliographical references (pages 338-357) and index.
Keywords: Communist Party of the Philippines (1902-1935) -- History; Communism -- History. -- Philippines; Philippines -- Politics and government